Modelling consumers' environmental responsibility and understanding of eco-labels: a conceptual framework for empirical research in Malaysia - Taufique, Khan Md Raziuddin; Siwar, Chamhuri Bin; Talib, Basri Abdul Abdul; Chamhuri, Norshamliza (© 2014 Inderscience Enterprises Ltd., 2018)
This article was published in the International Journal of Green Economics [© 2014 Inderscience Enterprises Ltd.] The Article's website is at:https://ukm.pure.elsevier.com/en/publications/modelling-consumers-environmental-responsibility-and-understandin